Influence of Textile Structure on the Hygroscopic Behavior of Bamboo Textile-Reinforced Polymer. Issue 16 (28th November 2022) - Chang, Chun-Wei; Chang, Feng-Cheng
ABSTRACT: Although bamboo fiber-reinforced polymer has been extensively studied, its utilization has been limited by its unfavorable performance. This study developed a non twisting bamboo textile-reinforced polymer (BTRP) through vacuum resin transfer molding and then used two weaving methods, different layers, different edge treatments, two stacking sequences, and two sizes as factors to investigate the effect of woven structures on the hygroscopic behavior of BTRP, such as water absorption, diffusion, dimensional stability, and moisture transportation. The differences in the results of long-term immersion and the swelling at different locations of BTRP were also examined. The results of this study indicate that the weaving method directly affected the water absorption from the fiber area and that the size of the specimens affected the saturation rate. The swelling behavior differed with the weaving method and number of layers, which indicates that rate of water ingress and transverse fiber swelling were the reasons that cause the different swelling behavior. This study found that moisture may be transferred differently through different parts of BTRP due to variations in fiber saturation. Moreover, the analysis of the center and periphery of BTRP specimens indicated that textile structure significantly affected water uptake and indirectly caused two moisture transport mechanisms.